2003
DOI: 10.1007/s00228-002-0529-3
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6*10 alleles do not determine plasma fluvoxamine concentration/dose ratio in Japanese subjects

Abstract: Our results indicate that CYP2D6*10 genotypes do not exert significant effects on FV C/D ratio. As CYP2D6 genotypes differ with ethnic background, further studies should be conducted in different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…For example, a lower antidepressant response or remission is reported for UMg and PMg (Kawanishi et al 2004;Tsai et al 2010;Rau et al 2004). However, several studies failed to report such an association: with fluvoxamine (Gerstenberg et al 2003;Ohara et al 2003); with citalopram (Peters et al 2008;Mrazek et al 2011);with paroxetine (Gex-Fabry et al 2008); with paroxetine and mirtazapine (Murphy et al 2003); with fluoxetine and nortriptyline (Roberts et al 2004); with escitalopram and nortriptyline (Hodgson et al 2014); with several antidepressants (Grasmader et al 2004;Serretti et al 2009). …”
Section: Introductionmentioning
confidence: 91%
“…For example, a lower antidepressant response or remission is reported for UMg and PMg (Kawanishi et al 2004;Tsai et al 2010;Rau et al 2004). However, several studies failed to report such an association: with fluvoxamine (Gerstenberg et al 2003;Ohara et al 2003); with citalopram (Peters et al 2008;Mrazek et al 2011);with paroxetine (Gex-Fabry et al 2008); with paroxetine and mirtazapine (Murphy et al 2003); with fluoxetine and nortriptyline (Roberts et al 2004); with escitalopram and nortriptyline (Hodgson et al 2014); with several antidepressants (Grasmader et al 2004;Serretti et al 2009). …”
Section: Introductionmentioning
confidence: 91%
“…In parallel, certain mutations of the CYP2D6 (i.e. *5, *10) have been associated with decreased fluvoxamine (Gerstenberg et al, 2003a), paroxetine (Yoon et al, 2000) and fluoxetine metabolism (Yu et al, 2002b;Llerena et al, 2004), although not all studies support this finding (Ohara et al, 2003). However, the CYP2D6 genotype does not appear to influence the likelihood of responding or developing side-effects to fluoxetine in MDD (Gerstenberg et al, 2003b;Roberts et al, 2004).…”
Section: Dosagementioning
confidence: 61%
“…Sixteen studies met inclusion criteria, of which five looked at metabolism of a single bolus of SSRI in healthy adults [32][33][34][35] or after a limited number of doses, 36 and 11 investigated the effects of CYP450 genotypes on the blood levels of specific SSRIs in patients at steady state doses. [37][38][39][40][41][42][43][44][45][46][47] • As expected based on the genotype, three single bolus studies of SSRI (sertraline, fluoxetine, or citalopram) metabolism in healthy adults showed that, compared with EMs, CYP2C19 PMs had significantly reduced metabolic function and significantly lower plasma concentrations of drug metabolites. In PMs, the parent drug had longer halflife and reduced clearance, compared with EMs.…”
Section: Recommendations From the Egapp Working Groupmentioning
confidence: 88%